BRANDING DAN LABELLING UPAYA PENINGKATAN STRATEGI PEMASARAN UMKM RAIDA COLLECTION - Ningsih, Moriska Hesti; Nafisah, Durrotun; Sari, Dian Anita (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
ABSTRACT Micro, Small and Medium Enterprises Raida Collection is a service business located in one of the Rembang Regencies engaged in the field of tailoring services. In the Pre-survey assistance conducted by KKU (Business Work Lecture) students of YPPI Rembang University, problems faced by MSME owners were found in the form of a lack of ability in knowing the importance of labeling and branding in their businesses. This assistance activity aims to advance the quality of branding and labeling in rural tailoring businesses whose branding has not improved enough. Based on the existing problems, the KKU program activities are to create a business brand identity and labeling on finished products. Therefore, the results of the pre-survey were compiled into a method for solving problems in the form of a qualitative approach through a) Student pre-survey to the owner's place by interviewing, asking for permission and compiling a program of activities to be implemented b) Implementation of the program to create brand and labeling designs c) Monitoring and evaluation of program activities d) Closing and withdrawal. Therefore, from the problem factors faced, a KKU program was created which. Program implementation, monitoring and evaluation and finally closing and withdrawal. The results of the community service program that were implemented showed that MSMEs already have an identity in the form of the Raida Collection business brand and finished product labeling. Keywords: Mentoring, Identity, Branding, Labeling.